PENDIDIKAN ANAK PERSPEKTIF PSIKOLOGI DAN PENDIDIKAN ISLAM - Maharani, Dewi (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2018)
This research aims to describe and analyze various aspects of children's education and find the concept of children's education in the perspective of psychology and Islamic education. This type of library research research, data collection techniques using documentation, after the data collected and then analyzed with descriptive analysis and content analysis. The results show the first: the conception of children's education in a psychological perspective has four main dimensions namely, physical, psychological, spiritual, and social-cultural. Parenting education of children must be in accordance with the psychological condition of children with authoritative style. Second: educating with the perspective of Islamic education, will make children more healthy souls namely those who have excellent physical requirements, higher intellectual mental intelligence (IQ), mental health conditions / personality that develops and is stable in their emotional emotional mentality (EQ) is high (mental-social) and have the strength of faith and Islam. Third: The important role of psychology in Islamic education is to bridge the process of delivering knowledge so that it pays more attention to the psychology of each individual or student, because this will determine the parents or educators in transferring knowledge given to children.